Induction of Phenol Hydroxylase from Aspergillus niger and Its Optimization - Bilgi, Mesut; Peksel, Aysegul (WILEY-V C H VERLAG GMBH, 2022)
Phenol is a harmful substance that can be present in many industrial wastewaters. Chemical phenol removal is feasible, but the procedure is challenging and expensive. Biological phenol removal is possible under mild conditions with enzymes. Phenol hydroxylase is the main enzyme for phenol removal. In this study, phenol hydroxylase was induced from filamentous fungus Aspergillus niger. The results have shown that it is possible to use Aspergillus niger as a phenol hydroxylase source, but the enzyme has activity in limited temperature and pH conditions. The optimal working conditions of the enzyme are 30 degrees C and pH 6.5. The enzyme has moderate storage and thermal stability, and various compounds inhibit it.
Keywords: Aspergillus niger; biocatalysis; enzymes; phenol hydroxylase; ADENINE-DINUCLEOTIDE; DEGRADATION; YEAST; BIOTRANSFORMATION; BIODEGRADATION; IDENTIFICATION; ANIONS; ENZYME; Chemistry